PENGEMBANGAN RUMAH TERHADAP PENINGKATAN SUHU RUANG AKIBAT BERKURANGNYA RUANG TERBUKA HIJAU - Muhammad Chaidar Febriansyah; Safruddin Juddah (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2021)
Community growth triggers an increase in the need for housing, as is the case with BTP Housing at this time, community growth in this housing encourages the need for more space in the dwelling, and often residents develop houses without following existing rules, thus changing green open spaces to excessive space in the house. This study aims to explain the amount of reduction in green open space in the AE block BTP residential area assessed from the area of house development. This research uses quantitative research methods, with the method of analysis used is descriptive statistics that describe and explain the findings of the research. This analysis is an accumulation of basic data in the form of descriptions. Data collection was carried out by direct observation and structured interviews using a questionnaire. The results found that 83% of the total sample developed houses with an area of> 81% of built land. Then, 4% of the sample with a percentage area of 71% - 80% of built-up land, and then 11% of the sample with a percentage of the built-up land area of 61% - 70%, and then 2% of the total sample area of 51% - 60% of the built-up land. Then 94% of the sample developed houses horizontally with an area of 41 m2 - 61 m2 and 6% carried out horizontal developments covering an area of 20 m2- 40 m2. So that only 6% of the total sample can still make maximum use of green open spaces, and 94% are no longer able to feel the benefits of green open spaces and result in an increase in room temperature in the house.